Methodical instructions for laboratory work "Determination of dust content of atmospheric air" in the discipline "Ecology" - Vaskovets, L. A.; Yevtushenko, Nataliіa Serhiivna; Tverdokhliebova, Natalia Yevheniivna (Національний технічний університет "Харківський політехнічний інститут", 2026)
Air quality characterizes the suitability of chemical, physical and biological factors of the air environment for the vital activity of living organisms. A change in the composition and properties of atmospheric air as a result of the entry or formation of physical, biological factors and (or) chemical compounds in it, which can adversely affect human health and the state of the natural environment, indicates its pollution and deterioration of quality [1]. The results of studies published in the European Heart Journal assure that in Europe the impact of various sources of atmospheric air pollution leads to 790 thousand additional deaths, of which 659 thousand deaths occur in the 28 countries of the European Union (EU) and 8.8 billion - worldwide. Studying individual countries, researchers found that air pollution causes additional mortality. The highest number of such cases (more than 200 per 100 thousand population) is in Bulgaria, Ukraine, Croatia and Romania (life expectancy (LE) in these countries is 3 or more years lower). In Germany – 154 thousand per 100 thousand population (LE – 2.4 years lower); in the UK – 98 respectively (LE – 1.5 years). The best air quality is in Norway, where the level of atmospheric pollution is significantly lower than the safety standards set by the WHO, which are stricter than the EU standards [2]. The European Alliance of Independent and Non-Governmental Organizations, Doctors, Environmentalists and Activists European Public Health Alliance (EPHA) has calculated the losses of residents of 432 EU cities due to air pollution. In total, they amount to €166 billion annually - an average of €1,276 per inhabitant. WHO experts emphasize the particular seriousness of health problems of residents of large cities due to air pollution with dust, especially fine particles. Today, most deaths are explained by the impact of microscopic dust with a diameter of less than 2.5 microns (PM2.5), which settles in the lungs and causes changes in the respiratory and circulatory systems. In 1990, about 1 million people died prematurely in Europe from its effects. According to forecasts, 70% of residents of European cities will live in areas where hygienic standards for dust are exceeded. The situation with atmospheric air pollution is also difficult in Ukraine. The pollution level of many cities of Ukraine is characterized by an increased content of suspended solid particles that enter the atmosphere during the combustion of organic fuels (coal and fuel oil), garbage at city landfills, industrial production, construction of structures and transport roads [6]. From stationary sources of pollution into the atmospheric air of Ukraine in 2018–2019, 316–310 thousand tons of solid particles entered the atmospheric air. Of these, microscopic dust with a diameter of more than 2.5 microns and less than 10 microns – 54–66 thousand tons, with a diameter of less than 2.5 microns – 24–2.5 thousand tons, soot – 5.9–5.8 thousand tons [3, 4]. To determine the danger of dust pollution of atmospheric air to human health and the environment, the concentration of suspended solid particles is measured in it. For this purpose, various methods and devices are used that take into account the dispersion of these particles.
Keywords: methodical instructions; laboratory work; ecology; atmospheric air; dust content; environment